Development of Ular Tangga SIAGA Media as a Counseling Tool to Improve Interpersonal Communication - Rizky, Alfida Isabella; Syarifudin, Syarifudin (Institut Agama Islam Negeri Kerinci, Indonesia, 2025)
Low levels of interpersonal communication skills among students frequently impede counseling effectiveness and social interaction in school settings. This research aimed to develop a counseling medium in the form of a board game, Ular Tangga SIAGA (SIAGA Snakes and Ladders), as an innovative tool to enhance students’ interpersonal communication, particularly aspects of openness and empathy. The study employed the Research and Development (R&D) method using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation. In the analysis phase, field studies were conducted through questionnaires and interviews with several stakeholders at SMP Negeri 1 Loa Janan to identify communication barriers. The media was then designed and developed using Canva and Microsoft Word, based on the identified counseling needs. During the development phase, the prototype was refined and prepared for expert validation. The evaluation phase involved validation by a Guidance and Counseling (BK) teacher, language experts for the truth or dare cards, and material experts to determine the media’s feasibility. The results indicated high validity scores for content (90%), media (80%), and educational aspects (92.4%). Quantitative observations further showed improvements in students’ openness and empathy during counseling interactions. Overall, Ular Tangga SIAGA demonstrates strong pedagogical feasibility and offers a culturally responsive, engaging, and safe medium for facilitating interpersonal communication in school counseling practices